Local complications of acute pancreatitis and methods of their instrumental diagnosis - S. I. Remizov; A. V. Andreev; V. M. Durleshter; S. A. Gabriel; Yu. S. Kuznetsov; O. V. Zasyadko; G. A. Levchenko (Вестник хирургии имени И.И. Грекова)
The literature review considers the characteristics of local complications in the classifications of acute pancreatitis, as well as analyzed the effectiveness of modern methods of their diagnosis. Understanding the morphology of changes occurring in the pancreas and parapancreatic tissue in acute pancreatitis is of great importance, as it often determines the tactics of surgical treatment. Modern diagnostic methods for local complications of acute pancreatitis, such as contrast-enhanced ultrasound, endoscopic ultrasound, computed tomography, magnetic resonance imaging and cholangiopancreatography are highly informative, but the effectiveness of their use depends on the duration of the disease and the type of local complications, which makes to apply the differentiated approach to their use.